(NH4)2V7O16 Microbricks as a Novel Anode for Aqueous Lithium‐Ion Battery with Good Cyclability. Issue 48 (29th July 2021) - Ma, Yining; Wu, Mingchen; Jin, Xiaodong; Shu, Rui; Hu, Chenchen; Xu, Tongxiang; Li, Jing; Meng, Xinyu; Cao, Xun
Abstract: Searching for novel anode materials to address the issues of poor cycle stability in the aqueous lithium‐ion battery system is highly desirable. In this work, ammonium vanadium bronze (NH4 )2 V7 O16 with brick‐like morphology has been investigated as an anode material for aqueous lithium‐ion batteries and Li + /Na + hybrid ion batteries. The two novel full cell systems (NH4 )2 V7 O16 ||Li2 SO4 ||LiMn2 O4 and (NH4 )2 V7 O16 ||Na2 SO4 ||LiMn2 O4 both demonstrate good rate capability and excellent cycling performance. A capacity retention of 78.61 % after 500 cycles at 300 mA g −1 was demonstrated in the (NH4 )2 V7 O16 ||Li2 SO4 ||LiMn2 O4 system, whereas no capacity attenuation is observed in the (NH4 )2 V7 O16 ||Na2 SO4 ||LiMn2 O4 system. The reaction mechanisms of the (NH4 )2 V7 O16 electrode and impedance variation of the two full cells were also researched. The excellent cycling stability suggests that layered (NH4 )2 V7 O16 can be a promising anode material for aqueous rechargeable lithium‐ion batteries. Abstract : Recharging your batteries : Brick‐like (NH4 )2 V7 O16, which features an open‐layered structure with two NH4 + ions residing in the V7 O16 layers, undergoes ammonium ion extraction and insertion processes during cycling. Two novel full cell systems, (NH4 )2 V7 O16 ||Li2 SO4 ||LiMn2 O4 and (NH4 )2 V7 O16 ||Na2 SO4 ||LiMn2 O4 (shown), both demonstrate good rate capability and excellent cycling performance, thus suggesting that the layered (NH4 )2 V7 O16 could be a promising anode material for aqueous rechargeable lithium‐ion batteries.